2008
DOI: 10.1021/ma071797i
|View full text |Cite
|
Sign up to set email alerts
|

High Molar Mass Poly(ε-caprolactone) by Means of Diphenyl Bismuth Ethoxide, a Highly Reactive Single Site Initiator

Abstract: Diphenylbismuth ethoxide, Ph 2 BiOEt, initiates the ring-opening polymerization of ε-caprolactone via a coordination-insertion mechanism. The matrix assisted laser induced desorption and ionization-time-offlight (MALDI-TOF) mass spectra proved the formation of one ethyl ester and one CH 2 OH endgroup. The reactivity of this initiator is high enough to allow even for polymerizations at 20 °C. At 120 °C the reactivity of Ph 2 BiOEt is lower than that of tin(II) 2-ethylhexanoate (SnOct 2 ) + ethanol, whereas belo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 49 publications
0
20
0
Order By: Relevance
“…The polymerization slows down at high conversion mainly due to the consumption of monomer and perhaps due to the increase in viscosity of the reaction mixture. In this connection, it should also be taken into account that Ph 2 BiOEt is much more active as an initiator than BiHex 3 7. All these findings together suggest that Ph 3 Bi needs activation by side reaction yielding Ph 2 BiOR groups, before it can initiate the ROP of ε CL.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The polymerization slows down at high conversion mainly due to the consumption of monomer and perhaps due to the increase in viscosity of the reaction mixture. In this connection, it should also be taken into account that Ph 2 BiOEt is much more active as an initiator than BiHex 3 7. All these findings together suggest that Ph 3 Bi needs activation by side reaction yielding Ph 2 BiOR groups, before it can initiate the ROP of ε CL.…”
Section: Resultsmentioning
confidence: 95%
“…The most efficient and the most widely studied polymerization mechanism of lactones, cyclic diesters, and cyclo‐carbonates is the so‐called coordination insertion mechanism,1–6 which goes back to a speculative formulation of Dittrich and Schulz 1. This mechanism which is exemplarily outlined for Ph 2 BiOEt7 in Equation (1) and (2) is characteristic for initiation with covalent metal alkoxides. As recently demonstrated by Penczek and coworkers8, 9 and Kricheldorf et al,10 this mechanism is also operating in the case of Sn(II) 2‐ethylhexanoate (SnOct 2 ) which is the most widely used initiator/catalyst for the technical production of biodegradable polyesters.…”
Section: Introductionmentioning
confidence: 99%
“…From polymerizations initiated by Ph 2 BiOEt23 or dry Ph 3 Bi35 it was meanwhile learned that the molar masses of the polylactones are strongly influenced by the presence of moisture or by addition of an alcohol as cocatalyst. Therefore, a small series of polymerizations was performed with the purpose to study the influence of the conditions used for the preparation of the reaction mixture on the resulting molecular weights.…”
Section: Resultsmentioning
confidence: 99%
“…Higher molecular weights and better control of the chain‐growth via the M / I ratio may be expected from single‐site catalysts, and our recent study of Ph 2 BiOEt indeed fulfilled these expectations. Ph 2 BiOEt23 is typically prepared from diphenyl bismuth bromide (Ph 2 BiBr),24 and this situation prompted us to elucidate, if Ph 2 BiBr itself might be an useful initiator and catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…Most examples of such coordination polymers reported to date are based on carboxylates (Stavila et al, 2004;Chen et al, 2008Chen et al, , 2011Jiang et al, 2008;Andrews et al, 2009;Thirumurugan et al, 2010;Anjaneyulu and Swamy, 2011;Wibowo et al, 2011;Anjaneyulu et al, 2012) and nitrogen-containing donor ligands (Morsali, 2006;Morsali and Mahjoub, 2006;Tershansy et al, 2007). Additionally, poly meric bismuth alkoxides (Whitmire et al, 1992;Roggan et al, 2005;Kricheldorf et al, 2008;Breunig et al, 2009b) have been reported as well as coordination polymers with sulfur-or seleniumcontaining donor ligands (Barton et al, 2000;Yim et al, 2000;Briand et al, 2012). Bismuth halides and pseudo halides are also capable of forming coordination polymers (Clegg et al, 1992(Clegg et al, , 1993Wang et al, 1997;Breunig et al, 2009a;Erbe et al, 2010;Koch and Ruck, 2010), and additionally, aromatic π donors (Silvestru et al, 1999;Mehring and Schürmann, 2001;Schmidbaur and Schier, 2008;Auer et al, 2009;Caracelli et al, 2013), organometallic ligands (Roggan et al, 2005), hexacyanoferrates (Perera et al, 2011), and polyoxometallates (Xu et al, 2007) were shown to bridge bismuth atoms to give unusual coordination polymers.…”
Section: Introductionmentioning
confidence: 99%